Estimation of genetic parameters for post-weaning body weights in New Zealand White rabbits reared under agroclimatic conditions of Sikkim - Bhushan, Bharat; Ahlawat, S P S (The Indian Journal of Animal Sciences, 2012)
Data on 403 progenies of 41 sires of New Zealand White rabbits on body weights at different ages during post-weaning period were used to study the genetic and phenotypic parameters. The analysis of variance showed nonsignificant effects of season of birth, sex and sire on body weight at different ages except the 8- week-body weight which was significantly (P£0.05) higher in season 2 than that in season 1. Linear regression of weight on litter weight at weaning was significant (P£0.05) for 6- week-body weight. Effect of dam/sire was also significant (P£0.05) for all the body weight traits. The average body weight of rabbits ranged from 0.53±0.01 to 1.94±0.03 kg from 6 to 24 weeks of age. The estimates of heritability for these traits ranged from 0.18±0.14 to 0.38±0.18, 0.73±0.22 to > 1.00 and 0.36±0.11 to 0.99±0.12 from sire, dam and sire+dam components, respectively. The positive and high genetic and phenotypic correlations between most of body weights were also observed.